A Comparative Study of the Electrochemical Properties of Mineral and Coal Pyrite - Ximeng Zhu (The Minerals, Metals and Materials Society, 1991)
The electrochemical behavior of mineral and coal pyrites in stirred and quiescent alkaline boratelsulfate solutions @H 7.9-10.5) have been investigated using cyclic voltammetry. Significant differences in the electrochemical response of these pyrites were observed. At the mineral pyrite surface, three anodic peaks at about -0.8 V, -0.1 V and +0.5 V (SCE) have been detected along with their corresponding reduction peaks. The first two peaks correspond to FeIFeOI) and FeOI)lFe(III) oxidation. The third peak is present for quiescent conditions but disappears as a distinct peak when the electrolyte is stirred. In the upper voltage region +0.30V (SCE), the current increases markedly during stirring and the reactions correspond to the oxidation of pyrite with the formation FeOII) oxides plus elemental sulfur. Also there is evidence that Fe oxy-ions form. Coal pyrites, under rapid sweep conditions display only the first two anodic peaks, the associated reduction peaks and an additional reduction peak corresponding to one or more of the high voltage oxidation products. After prolonged exposure to high potentials, coal pyrite displays reactions similar to those of mineral pyrite but at much higher current densities demonstrating the much higher reactivity of the coal pyrite. The reactivity sequence was Upper Freeport coal pyrite > Pittsburgh coal pyrite > mineral pyrite.